If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5k=(-2-8k)-7
We move all terms to the left:
5k-((-2-8k)-7)=0
We add all the numbers together, and all the variables
5k-((-8k-2)-7)=0
We calculate terms in parentheses: -((-8k-2)-7), so:We get rid of parentheses
(-8k-2)-7
We get rid of parentheses
-8k-2-7
We add all the numbers together, and all the variables
-8k-9
Back to the equation:
-(-8k-9)
5k+8k+9=0
We add all the numbers together, and all the variables
13k+9=0
We move all terms containing k to the left, all other terms to the right
13k=-9
k=-9/13
k=-9/13
| 7x+62=3x+90 | | 1x=224 | | 8(2x)=28 | | 5a-7=a-15 | | 6x+25-x=32+13 | | 2x+3+4x5=32 | | 5r=(-3r-9)-7 | | 4x-22x=17 | | 6g+5=-2-4g | | -5f-8=6f+4 | | 2m-10=7m | | 4x-6=3+3 | | 6x+8=7-2x | | –2x+10=4x–2 | | –2p+10=4p–2 | | 3c–1=c+9 | | 100(z-0.2=-10(5z+0.8) | | 6x-2=(4x+5)+25 | | 3x+27=5 | | 2x+8=5x+3.5 | | 50+5.5x=18.50+7.75 | | 15+c=19.50 | | 8b+8=6+6b | | k/6+8=5k/6+8=5 | | 4=29x^2+203 | | 3/4x+1=5/6x-2 | | 5(2-x)-(x-9)=2x+27 | | 0.7x-1.4=0.2+1.6 | | 3x+1=+x7 | | 5x+6=46* | | 8b-3b+4=11 | | X+7=2x+37 |